Pigeonpea composite collection and identification of germplasm for use in crop improvement programmes - Upadhyaya, Hari D.; Reddy, K.N.; Sharma, S.; Varshney, Rajeev K.; Bhattacharjee, Ranjana; Singh, S.; Gowda, C.L.L. (Cambridge University Press, 2011)
Pigeonpea (Cajanus cajan (L.) Millsp. is one of the most important legume crops as major source for proteins, minerals and vitamins, in addition to its multiple uses as food, feed, fuel, soil enricher, or soil binder, and in fencing, roofing and basket making. ICRISAT's genebank conserves 13,632 accessions of pigeonpea. The extensive use of few parents in crop improvement is contrary to the purpose of collecting a large number of germplasm accessions and has resulted in a narrow base of cultivars. ICRISAT, in collaboration with the Generation Challenge Program, has developed a composite collection of pigeonpea consisting of 1000 accessions representing the diversity of the entire germplasm collection. This included 146 accessions of mini core collection and other materials. Genotyping of the composite collection using 20 microsatellite or simple sequence repeat (SSR) markers separated wild and cultivated types in two broad groups. A reference set comprising 300 most diverse accessions has been selected based on SSR genotyping data. Phenotyping of the composite collection for 16 quantitative and 16 qualitative traits resulted in the identification of promising diverse accessions for the four important agronomic traits: early flowering (96 accessions), high number of pods (28), high 100-seed weight (88) and high seed yield/plant (49). These accessions hold potential for their utilization in pigeonpea breeding programmes to develop improved cultivars with a broad genetic base. Pigeonpea germplasm has provided sources of resistance to abiotic and biotic stresses and cytoplasmic-male sterility for utilization in breeding programmes.